Comparison of Albumin-Bilirubin, Platelet-Albumin-Bilirubin, and Child-Pugh scores to predict overall survival in patients with stage C hepatocellular carcinoma with liver cirrhosis treated with c-TACE - Wu, Fei; Zhang, Zhihong; Liu, Shanshan (Frontiers in Oncology, 2025)
PurposeThis study aimed to evaluate and compare the prognostic performance of Albumin-Bilirubin (ALBI), Platelet-Albumin-Bilirubin (PALBI), and Child-Pugh (CP) scores in predicting overall survival (OS) among patients with stage C hepatocellular carcinoma (HCC) with liver cirrhosis undergoing conventional transcatheter arterial chemoembolization (c-TACE).MethodsWe performed a retrospective cohort analysis of 151 cirrhotic patients with Barcelona Clinic Liver Cancer (BCLC) stage C HCC treated with c-TACE between 2017 and 2021. Pretreatment CP scores, ALBI, and PALBI were recorded, and their associations with OS were analyzed using Kaplan-Meier methods and receiver operating characteristic (ROC) curve analysis. Multivariate Cox models were used to determine independent survival predictors.ResultsThe median OS for the entire study cohort was 18.8 months (95% CI: 11.294-26.306 months). CP score, ALBI grade and PALBI grade were significantly correlated with OS (all P<0.05). Survival analysis revealed dose-dependent relationships: CP classes A and B demonstrated median OS of 22.9 vs 9.9 months (P<0.05), ALBI grades 1–3 corresponded to median OS of 25.7, 12.7, and 3.8 months respectively (P<0.05), PALBI grades 1–3 showed median OS of 25.7, 10.1, and 8.5 months (P<0.05). The area under the receiver operating characteristic curve (AUROC) values of CP score, ALBI grading, ALBI score, PALBI grading and PALBI score were 0.572, 0.550, 0.595, 0.619 and 0.637, respectively. Compared with the CP score and ALBI, PALBI showed a better predictive effect in patients with stage C hepatocellular carcinoma with cirrhosis treated with c-TACE. Multivariate analysis showed that CP grade, ALBI grade, PALBI grade, Portal vein invasion, and the number of c-TACE were independent predictors affecting the survival period of patients.ConclusionIn cirrhotic patients with BCLC stage C HCC undergoing c-TACE, the PALBI scoring system emerged as a more reliable prognostic indicator than CP and ALBI assessments, showing enhanced discriminative capacity for survival outcomes.